Oscilações devidas aos sobre-harmônicos de maré na Baía de Sepetiba (RJ) e sua influência nas correntes residuais - Fonseca, Sabrina Aparecida Ramos da (2019)
Sepetiba Bay (SB) is a coastal lagoon, where the circulation is mainly forcing by the tide. The ecosystem is connected to Ilha Grande Bay, forming the Ilha Grande and Sepetiba bay (IGSB) complex, which has a natural oscillation period of ~ 6h. One of the main objectives of this work was to investigate if winds and tide influence on the origin of this natural oscillation. The numerical experiments results showed that local winds do not generate oscillations with periods close to the period of natural oscillation of the BIGS system (~ 6h) and also we conclude that shallow water tide components generated within the SB do not excite the seiche in the system. The SB resonance could occur between the shallow water components, which enter in the SB coming from the platform and the seiche. A complete study on the origin and behavior of the asymmetries recorded within the SB is presented, as well as a study on the residual flow of currents in this water body. In addition, the residual flow in SB was 90% barotropic. The influence of non-barotropic component increased in the adjacent regions, in the northeast part of the bay, near to the mouth of the rivers. This behavior was maintained throughout the eastern part of the bay, obtaining similar values in the vicinity of the Marambaia sandbar.